Agroforestry discussion pack - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Agroforestry research: approaches to the design of agroforestry systems with emphasis on buffer zone development in the rain forests of West Africa